From Doctrine To Rationality: Harun Nasution's Thought On An Objective Approach In The Study Of Islamic Theology - Utomo, Fendi (DAS CONFERENCE INTERNATIONAL SERIES, 2025)
This article examines the development of Islamic theological schools and the influence of political factors in their formation, with a specific focus on Harun Nasution's critique of conservative theological education in Indonesia. The research demonstrates that the diversity of Islamic theological currents such as Khawarij, Murji'ah, Mu'tazilah, Ash'ariyyah, Maturidiyyah, Qadariyyah, and Jabariyyah emerged as responses to the political and intellectual dynamics throughout Islamic history. Despite their diversity, these schools remained within the broader framework of Islam, with Ash'ariyyah and Maturidiyyah, later known as Ahlussunnah wal Jama'ah, proving to be the most enduring to date. Through a philosophical and objective approach, Harun Nasution critically addresses the prevailing tendency in Indonesian theological education to exclusively focus on the Ash'ariyyah school in a doctrinal manner, which consequently leads to distortions in understanding. He proposes a more comprehensive pedagogical method that encompasses the history, core concepts, and inter-school debates, including the contentious issue of reason and revelation that sparked intense discussions among Mu'tazilah, Ash'ariyyah, and Maturidiyyah. This study concludes that a broad and objective understanding of various Islamic theological schools is crucial to prevent narrow fanaticism and to enable individuals to choose a theological perspective that aligns with their intellectual and spiritual inclinations.